Load Contact Analysis and Strength Calculation of Spur Gear - Wang Yunzhi (Jixie chuandong)
Through tooth contact analysis（ TCA） and loaded tooth contact analysis（ LTCA）,the meshing process of spur gear pair is simulated. Based on this,combining with the elasticity theory,the contact stress on each meshing point are calculated. On the basis of the stress effect matrix of the finite element method,the bending stress states at the tooth root are analyzed. According to the calculation results of LTCA,an approximate calculation method of spur gear is proposed,the life of spur gear pair is calculated. Finally,a software of meshing analysis and modification designing of spur gear tooth flank is developed based on the MATLAB language.